Social skills and aggressiveness in secondary students during confinement - Obregón López, Giuliana Margarita (2023)
The general objective of the research was to identify the relationship between social skills and aggressiveness in 4th grade high school students of an Educational Institution in Lima. In the methodological field, the quantitative approach, the hypothetical deductive method, type of basic research, level descriptive correlational and the non-experimental cross-sectional design were used. We used two instruments with validity and reliability for data compilation, which were the Check List Social Skills of Goldstein adapted nationally by Tomas (1995), and the Questionnaire of Aggression of Buss and Perry adapted to our environment by Matalinares et al. (2012). Likewise, 71 students from 4th grade of secondary school participated. To process the results, Spearman’s Rho statistic was used and the value of -, 374 ** was found and the significance value is 0.001, being less than 0.05, which indicates that there is a significant, negative and low correlation. Finally, it is concluded that, at a higher level of social skills, lower levels of aggressiveness or at lower levels of social skills, higher levels of aggressiveness.